2011
DOI: 10.3390/ijerph8083232
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Mixed with Energy Drinks: Consumption Patterns and Motivations for Use in U.S. College Students

Abstract: Binge drinking in college students is widespread and known to cause significant harms and health hazards for the drinker. One factor that may be exacerbating hazardous drinking in young people is the new popular trend of consuming alcohol mixed with energy drinks (AmED). However, rates of AmED use and motivations for AmED consumption in college students have not been well established. In this study, 706 undergraduate college students from a university in the United States participated in a web-based survey tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
136
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(157 citation statements)
references
References 26 publications
17
136
0
4
Order By: Relevance
“…Several questions were based on four self-administered questionnaires used in previous studies dealing with the same theme. 6,[16][17][18] The questionnaire was pretested with a sample of the target population to ensure respondents clearly understood it. A few participants found that some questions had repetitive answer choices and that the questionnaire was too long.…”
Section: Methodsmentioning
confidence: 99%
“…Several questions were based on four self-administered questionnaires used in previous studies dealing with the same theme. 6,[16][17][18] The questionnaire was pretested with a sample of the target population to ensure respondents clearly understood it. A few participants found that some questions had repetitive answer choices and that the questionnaire was too long.…”
Section: Methodsmentioning
confidence: 99%
“…Dans la dernière année 51 % : 1-51 jours (faibles consommateurs) 10 % ≥ 52 jours (forts consommateurs) États-Unis (n = 585) 18 % ≥ 1 fois dans la dernière semaine 38 % ≥ 1 fois (Velazquez, Poulos, Latimer & Pasch, 2012) Ghana (n = 180) 62 % ≥ 1 fois dans la dernière semaine avec 80 % qui consomment 1-2 BÉ/semaine et 21 % qui consomment 3-4 BÉ/semaine (Buxton & Hagan, 2012) Ces recherches révèlent que la consommation de BÉ est un phénomène répandu chez les universitaires aux États-Unis et dans quelques autres pays, 18 % à 65 % des répondants en ayant consommé dans la ou les deux dernières semaines (Buxton & Hagan, 2012 ;Marczinski, 2011 ;Pettit & DeBarr, 2011 ;Price, Hilchey, Darredeau, Fulton, & Barrett, 2010 ;Velazquez, Poulos, Latimer, & Pasch, 2012). De plus, entre 38 % et 70 % des répondants auraient consommé des BÉ au moins une fois dans le dernier mois.…”
Section: Classification Des Boissons éNergisantesunclassified
“…(Miller, 2008a ;Miller, 2008b ;Velazquez, Poulos, Latimer, & Pasch, Liens entre consommation de boissons énergisantes et consommation de psychotropes chez les jeunes 2012 ; Malinauskas, Aeby, Overton, Carpenter-Aeby, & Barber-Heidal, 2007). Le tableau indique aussi qu'une forte proportion des universitaires questionnés en ont déjà consommé, soit de 31 % à 81 % des participants Ballistreri & Corradi-Webster, 2008 ;Berger, Fendrich, Chen, Arria, & Cisler, 2011 ;Marczinski, 2011 ;Oteri, Salvo, Caputi, & Calapai, 2007). Seulement quelques études quantifient le nombre de BÉ consommées par semaine (Buxton & Hagan, 2012 ;Marczinski, 2011) ou par occasion (Pettit & DeBarr, 2011).…”
Section: Classification Des Boissons éNergisantesunclassified
See 1 more Smart Citation
“…Combining caffeine with ethanol during binge drinking may stem from the popular belief that caffeine antagonizes those intoxicating effects of alcohol (Reissig et al, 2009). For example, college students report consuming energy drinks combined with alcohol to quicken the onset of intoxication, and to reduce fatigue after drinking (Marczinski, 2011). Moreover, epidemiologic studies have shown that energy-drink users tend to show increased levels of alcohol consumption.…”
Section: Introcutionmentioning
confidence: 99%